DOR dan Drama Keadilan (Analisis Sosiologi Sastra) - Khothibul Umam (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The study of play scripts is one of the rare literary studies. One reason is because the object is very rare. The highly productive Indonesian play script writer is Putu Wijaya. Putu Wijaya wrote many stories with many themes, one of which was titled DOR, which raised social and justice themes. The theory used to analyze DOR is the sociology of literature with the help of psychology and law science through literature study with the method of reading, listening and note taking. In DOR, there are various kinds of character clashes between characters in responding to a case. Justice that tries to be sought in the narrative of this play always collides with various problems, where the premise becomes a kind of reflection on social phenomena that occur in the real world. Even though it was written decades ago, DOR still feels relevant to the condition of society, especially its relation to the world of law enforcement and the search for justice, which is increasingly bleak and unclear. As a work of art, DOR is capable of photographing various kinds of legal world phenomena with all its cross-clashes. The clash of character or character really represents all the complexities of legal problems in Indonesia. Where various interests take part in determining the results of justice seeking.